Q: -6x plus 3 equals -7-5x

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

6x + 3 = 2x + 5 4x = 2 x=1/2

74

x2 + 6x + 12 = 0 x2 + 6x + 9 = -3 (x + 3)2 = -3 x + 3 = ± √-3 x = -3 ± i√3

5

It is an equation and the value of x is 4

Related questions

6x plus 3 equals 8x plus 14 when solved mathematically is equal to x = -5.5.

3+6x = 4x+9 6x-4x = 9-3 2x = 6 x = 3

6x plus 3 equals to 8x plus 14 would lead to x = - 5.5.

x = -3

y=(6x-5)/3

-4x+3 = 23+6x -4x-6x = 23-3 -10x = 20 x = -2

9x + 3 - 6x - 2 = 3x + 1

6x + 2 = 6 6x = 4 x = 2/3

6x + 3 = 2x + 5 4x = 2 x=1/2

It is: 3x2+6x-11 = 0

-15 = 6x + 3 - 3-15 = 6x (3 - 3 = 0)-2.5 = x (-15/6)

x=-6,5